PEMBELAJARAN IPS DENGAN METODE LIFE SKILL OF PORTOFOLIO UNTUK SMP - Sribudi Karyadi; R Gunawan Sudarmanto; Iskandarsyah Iskandarsyah (Faculty of Teacher Training and Education, University of Lampung, 2013)
This research was held to construct IPS learning with life skill of portofolio method at class IX of SMPN 22 in 2012-2013. This learning research was planned and drawn up based on IXA and IXB SMPN 22 student’s life skills in 2012-2013. The type of this research is qualitative descriptive, based on SMPN 22 student’s life skills in class IX, through stages of exploration, colaboration, documentation and presentation. There are two kind of life skills were used in this reserach, they are common life skill and special life skill. Common life skill consist of individual skill, information quarry skill, social skill and group skill. As for special skill consist of documentation skill and appearance skill. The construction stages of IPS learning with life skill of portofolio method starts from mapping standard competetion and basic competetion, planning the IPS learning with life skill of portofolio method, planning of IPS learning, the erly stage of learning and IPS learning with life skill of portofolio method grouping, and last but not least is the stages of documentation. Thereform, IPS learning with life skill of portofolio method at class ix of SMPN 22 in 2012-2013 can increase the level of cognitive, affective, psycomotor and social skill.Keywords : Learning life skill of portofolio method and life skills